Identity of Colonial Architecture Preservation in Thakhek City Center - SIHAVONG, Saikhim; SENGONKEO, Luangphasy; SYHALATE, Phisit; INSYXIENGMAI, Sithixay; PHONGKHAMDENG, Phaichit (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper examines the conservation of colonial architecture in the center of Thakhek, which is a unique and historically significant feature of the city. Researching the historical context, architectural features and cultural values ​​of the buildings in the colonial era in Laos and efforts to conserve and promote them to become urban heritage. The research uses mixed methods, combining documentary research, observation from the field through surveys, measurements and interviews with local stakeholders. The findings reveal the challenges faced in preserving the colonial architecture at Thakhek, including limited resources. This research also highlights the potential benefits of preserving colonial architecture, such as promoting cultural tourism, promoting community pride and contributing to urban regeneration. The study concluded with recommendations to strengthen the preservation of colonial architecture in the center of Thakhek, emphasizing the need for a comprehensive preservation plan, increasing public awareness and cooperation between local stakeholders. This research contributes to the broader discussion on heritage conservation in Southeast Asia, offering insights into the challenges and opportunities of preserving colonial architecture in old urban areas in a context of rapid urban development.